Vascular Origin of Vildagliptin-induced Skin Effects in Cynomolgus Monkeys: Pathomechanistic Role of Peripheral Sympathetic System and Neuropeptide Y. (June 2014) - Hoffmann, Peter; Bentley, Phil; Sahota, Pritam; Schoenfeld, Heidi; Martin, Lori; Longo, Linda; Spaet, Robert; Moulin, Pierre; Pantano, Serafino; Dubost, Valerie; Lapadula, Dan; Burkey, Bryan; et al.
The purpose of this article is to characterize skin lesions in cynomolgus monkeys following vildagliptin (dipeptidyl peptidase-4 inhibitor) treatment. Oral vildagliptin administration caused dose-dependent and reversible blister formation, peeling and flaking skin, erosions, ulcerations, scabs, and sores involving the extremities at ≥5 mg/kg/day and necrosis of the tail and the pinnae at ≥80 mg/kg/day after 3 weeks of treatment. At the affected sites, the media and the endothelium of dermal arterioles showed hypertrophy/hyperplasia. Skin lesion formation was prevented by elevating ambient temperature. Vildagliptin treatment also produced an increase in blood pressure and heart rate likely via increased sympathetic tone. Following treatment with vildagliptin at 80 mg/kg/day, the recovery time after lowering the temperature in the feet of monkeys and inducing cold stress was prolonged. Ex vivo investigations showed that small digital arteries from skin biopsies of vildagliptin-treated monkeys exhibited an increase in neuropeptide Y–induced vasoconstriction. This finding correlated with a specific increase in NPY and in NPY1 receptors observed in the skin of vildagliptin-treated monkeys. Present data provide evidence that skin effects in monkeys are of vascular origin and that the effects on the NPY system in combination with increased peripheral sympathetic tone play an important pathomechanistic role in the pathogenesis of cutaneous toxicity.